2006
DOI: 10.1161/circulationaha.105.591446
|View full text |Cite
|
Sign up to set email alerts
|

Statins and Mortality Among Elderly Patients Hospitalized With Heart Failure

Abstract: Background— Small studies suggest that statins may improve mortality in patients with heart failure (HF). Whether these results are generalizable to a broader group of patients with HF remains unclear. Our objective was to evaluate the association between statin use and survival among a national sample of elderly patients hospitalized with HF. Methods and Results— A nationwide sample of 61 939 eligible Medicare b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(65 citation statements)
references
References 37 publications
(30 reference statements)
3
59
0
2
Order By: Relevance
“…270,271 Furthermore, retrospective analyses of trials in patients with coronary artery disease but without a history of HF demonstrated a reduction in the risk of development of HF and HF hospitalizations in patients taking statins. 272 However, 2 large, prospective, randomized trials failed to confirm these beneficial effects of statins in patients with established HF.…”
Section: Treatment Of Hyperlipidemia In Hf For the Indication Of Hf Amentioning
confidence: 99%
“…270,271 Furthermore, retrospective analyses of trials in patients with coronary artery disease but without a history of HF demonstrated a reduction in the risk of development of HF and HF hospitalizations in patients taking statins. 272 However, 2 large, prospective, randomized trials failed to confirm these beneficial effects of statins in patients with established HF.…”
Section: Treatment Of Hyperlipidemia In Hf For the Indication Of Hf Amentioning
confidence: 99%
“…What is surprising is that statins also improve heart function and survival in patients with non-ischemic heart failure [21][22][23][24]. Patients with severe heart failure without evidence of ischemic etiology have reduced all-cause mortality and are free from urgent transplantation on statin therapy [25].…”
Section: Clinical Trials With Statinsmentioning
confidence: 99%
“…Similar results were found by another report looking at hospital discharge diagnosis and prescription data gathered on Medicare patients; those heart failure patients who filled their prescriptions for statins had significantly lower morality rates. 17 An association of statins with lower mortality rates was also noted in the EuroHeart Failure survey. 18 The Controlled Rosuvastatin Multinational Trial in Heart Failure (CORONA) 15 was recently published.…”
Section: Reviewmentioning
confidence: 73%